Is Still's Disease an Autoinflammatory Syndrome? - Linda Rossi-Semerano; Isabelle Koné-Paut (Hindawi Limited, 2012)
Systemic juvenile idiopathic arthritis (sJIA), formerly called Still's disease, is officially classified as a subset of juvenile idiopathic arthritis (JIA). Beside arthritis, it is characterized by prominent systemic features and a marked inflammatory response. Even if it is still included in the group of juvenile arthritides, sJIA is set apart from all the other forms of JIA. This disorder has markedly distinct clinical and laboratory features suggesting a different pathogenesis. sJIA does not show any association with HLA genes or with autoantibodies and is characterised by an uncontrolled activation of phagocytes with hypersecretion of IL-1 and IL-6. Based on clinical and laboratory features, as well as on new acquisitions on the pathogenesis, it seems evident that sJIA is an autoinflammatory disease related to abnormality in innate immune system. The new insights on the pathogenesis of sJIA have therefore dramatically changed the approach to treatment, with the development of targeted treatments (anti-IL-1 and anti-IL-6 agents) more effective and safer than earlier medications.